Implementasi Sistem Informasi Berbasis Website Pada Gereja Ichtus Puildon Menggunakan Metode Waterfall - Gilberth Patrick Daniel; Ika Nur Fajri; Yoga Prisyanto (Journal of Information System Research (JOSH), 2025)
This research focuses on the development of a web-based information system for Ichtus Puildon Church, which faces issues in the management of congregation data that is still done manually. This process causes data to be easily lost and hard to access, as well as requiring more time and effort for report generation. The aim of this research is to design and implement an information system that can improve the efficiency of congregation data management. The approach used in this research is the Waterfall method, which includes problem identification, data collection through questionnaires, system analysis, and implementation. Testing is carried out using Black Box, White Box, and System Usability Scale (SUS) methods to evaluate the system's performance and user satisfaction. The results show that the application achieved a score of 74.2%, which falls into the "Good" category. Functional testing of login, menu access, and content management by the admin indicates that the system works well, provides a satisfactory user experience, and has the potential to improve the church's digital services.